WTO law and trade policy reform for low-carbon technology diffusion : common concern of humankind, carbon pricing, and export credit support - Ahmad, Zaker (World Trade Institute advanced studies, 2021)
"In [this book] Zaker Ahmad puts a spotlight on the crucial importance of dismantling market barriers, and offering incentives, to improve clean technology access and diffusion across borders. To that end, the author argues for a synergistic co-development of the international trade and climate legal regimes. Two case studies (one on carbon pricing, another on official export credit support) place the theoretical arguments in a practical trade policy setting. The emerging doctrine and principle of Common Concern of Humankind serves as the key theoretical and structural foundation of the work"--